Prevalence of COVID-19 Protective Behavior (The Use of Face Mask) Among Pedestrians in the Southwestern Regions of Iran: An Observational Study - Maryam Changizi; Hooshang Mohamadian; Bahman Cheraghian; Shokrollah Salmanzadeh; Fatemeh Maqsoodi; Sasan Ghorbani Kalkhajeh (Gonabad University of Medical Sciences, 2024)
Background: Protective behavior is recommended to prevent COVID-19. However, the existing gap is no reliable evidence of protective behavior in southern urban areas in Iran. This study aims to estimate the prevalence of face mask usage and shield use among pedestrians in the Abadan, Khoramshahr, and Shadegan southern cities of Iran.  Methods: This population-based cross-sectional study was conducted from June to August 2021 in the southwestern urban population of Iran. In this study, 7 425 pedestrians were selected from 85 neighborhoods. Sampling was conducted using a multi-stage method. The data were collected by observation passers on the street with a checklist and analyzed by SPSS software, version 26 statistical and WINPEPI software. The acceptable significance level was P<0.05. Results: A total of 55.4% of the subjects were men. The prevalence of face mask usage was 3990(53.8%) (95% CI, 52.7%-55%). The correct use of the face mask and shield were (38.5% and 0.4%), respectively. The use of a face mask was higher in men than women (54.3 vs 53%). Pedestrians under 10 years (39.2%) and over 70 years (44.7%) had the lowest use of the mask. The use of face mask was more in the evening and night (58.1% vs 54.3%), and a significant relationship was observed between the use of the face mask and age (P<0.05). Conclusion: The prevalence of the use of face mask is relatively low. Therefore, the possibility of controlling the infection may be difficult. Promoting media literacy, emphasizing the perceived benefits of preventative behavior, and setting rules may improve mask use.